2021
DOI: 10.1177/1932296820978399
|View full text |Cite
|
Sign up to set email alerts
|

How to Best Protect People With Diabetes From the Impact of SARS-CoV-2: Report of the International COVID-19 and Diabetes Summit

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus has rapidly involved the entire world and exposed the pressing need for collaboration between public health and other stakeholders from the clinical, scientific, regulatory, pharmaceutical, and medical device and technology communities. To discuss how to best protect people with diabetes from serious outcomes from COVID-19, Diabetes Technology Society, in collaboration with Sansum D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
1
14
0
5
Order By: Relevance
“…Significant health effects (including death and morbidity associated with hospitalization) were observed and seemed to preferentially affect older adults and those with comorbidities [6][7][8][9][10][11][12][13]. Research has demonstrated that comorbidities such as diabetes are important risk factors contributing to COVID-19 outcomes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant health effects (including death and morbidity associated with hospitalization) were observed and seemed to preferentially affect older adults and those with comorbidities [6][7][8][9][10][11][12][13]. Research has demonstrated that comorbidities such as diabetes are important risk factors contributing to COVID-19 outcomes [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is well described as a major comorbidity of hospitalized patients with COVID-19 [14][15][16]. Several studies have found associations between diabetes and greater odds of adverse clinical outcomes in COVID-19 including longer length of hospitalization, higher mortality rate, ICU admission, and mechanical ventilation [4,5,9,13,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Resilience was one of the topics addressed during the International COVID-19 and Diabetes Virtual Summit sponsored by the Diabetes Technology Society in collaboration with Sansum Diabetes Research Institute aiming to protect diabetic people from the severe effects of COVID-19. Thus, resilience is thought to be a gap of knowledge to be explored as even after vaccination, diabetic individuals can still face many difficulties [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data will continue to be valuable over the foreseeable future. Knowing where and who needs assistance allows responsible agencies to plan for the next wave of COVID-19 and for future pandemics to assist people dealing with housing, mental health, suicide and substance abuse issues [ 63 ].…”
Section: Discussionmentioning
confidence: 99%